1A.11: ASSOCIATION OF KIF6 AND HMGCR LOCI WITH CARDIOMETABOLIC PHENOTYPES AND RESPONSE TO STATIN THERAPY IN THE BRISIGHELLA COHORT. (June 2015) - Rosticci, M.; Marullo, L.; Cicero, A.F.G.; Magi, R.; Fischer, K.; Pervjakova, N.; D'Addato, S.; Rizzoli, E.; Massimo, G.; Giovannini, M.; Angelini, S.; Scapoli, C.; et al.
Abstract : Objective: Cardiovascular disease (CVD) represents the most common and lethal chronic disease worldwide. Lipids levels are the strongest risk factors for CVD and this is demonstrated by the fact that lipid-lowering statin therapy is largely used to prevent CVD. The role of the KIF6 gene in response to the statin therapy is controversial, and the biological mechanism through which it may act is still unknown. We investigated the role of KIF6 locus variants alone and their interaction with the well-established lipid locus at HMGCR in the variability of metabolic traits and in response to statin therapy in an Italian sample. Design and method: We genotyped two intronic rs20455, rs9462535 and a coding rs9471077 within the KIF6 gene, as well as two non-coding rs3761740 and rs3846662 at HMGCR. We tested the association of these SNPs with 19 cardiometabolic phenotypes and lipid-lowering therapy response in a sample of 1645 individuals from the Brisighella cohort (BC). Results: Established rs3846662 (Willer et al, Nat Gen 2013) at HMGCR is associated (P = 8.5x10-4) with LDL cholesterol (LDL-C) in BC. We did not find any significant association of KIF6 variants with response to statin therapy. We observe a locus-wide significant association at KIF6 between rs9471077 and APOB levels and rs20455 and HDL-C (P less than 0.001). rs3761740 at HMGCR showed an effect on systolic and diastolic blood pressure (SBP/DBP, P less than 0.007), which however wasn't significant after multiple testing correction. Conclusions: This is the first genetic study reported for Brisighella cohort, which confirms association with LDL-C at HMGCR locus. We noticed an effect of KIF6 variants on APOB and HDL-C, while we don't observe any effect on statin therapy. The study sample is relatively small to discover a common variant effect and might still be due to chance; therefore, we are seeking for replication in additional cohorts. These findings, if confirmed, might contribute to development of approaches for stratified patient care.